Food Selectivity and Its Implications Associated with Gastrointestinal Disorders in Children with Autism Spectrum Disorders - Valenzuela Zamora, Angel Francisco; Ramírez-Valenzuela, David Gerardo; Ramos Jimenez, Arnulfo (2022)
Food selectivity (FS) in children with autism spectrum disorders (ASD) is common, and its impact on a nutritional level is known. However, the etiology of gastrointestinal disorders (GID) related to alterations in the intestinal microbiota in children with ASD remains unclear. This article provides a narrative review of the literature on FS from the last 15 years, and its relationship with GID in children with ASD. Sensory aversion in ASD leads to food elimination, based on consistencies, preferences, and other sensory issues. The restriction of food groups that modulate the gut microbiota, such as fruits and vegetables, as well as the fibers of some cereals, triggers an intestinal dysbiosis with increased abundance in Enterobacteriaceae, Salmonella Escherichia/Shigella, and Clostridium XIVa, which, together with an aberrant immune response and a leaky gut, may trigger GID. It is observed that FS can be the product of previous GID. GID could provide information to generate a hypothesis of the bidirectional relationship between FS and GID. Emphasis is placed on the need for more studies with methodological rigor in selecting children with ASD, the need for homogeneous criteria in the evaluation of GID, and the adequate classification of FS in children with ASD.